CO2 emissions: a dynamic structural analysis - Vieira, Marco Aurelio; Ceretta, Paulo Sergio (Revista de Administração da UFSM, 2021)
Purpose - The purpose of this article is to analyze the impact of energy consumption and economic growth on CO2 emissions worldwide and to present the temporary evolution of CO2 emissions during the pandemic. Design/methodology/approach - The final sample was composed of 72 countries observed for a period of 15 years; the data were collected in the World Bank database. The analysis was performed using a structural dynamic data panel with fixed effects estimated by Maximum Likelihood. Findings - The results indicate that energy consumption affects CO2 emissions directly and positively. GDP per capita has a double effect, 1) it affects CO2 emissions directly and negatively and 2) indirectly, through the path of energy consumption, it has a positive effect contributing to the increase of CO2 emissions. Double effect on carbon emissions is also identified for fixed capital, 1) direct and indirect positive effect on CO2 emissions and 2) negative indirect effect via GDP per capita. Still, the population affects CO2 emissions directly and positively and, from another perspective, the population's indirect influence is confirmed, reducing CO2 emissions via energy consumption. Originality/value - It is concluded that the reduction of human activities due to forced confinement affected the global use of energy and contributed to the reduction of CO2 emissions in this period. It is suggested to government officials and the population in general to adopt post-pandemic measures related to the development of energy technology by alternative sources of energy.